A new species of Loneura Navás and taxonomic update of L. boliviana Williner and L. meridionalis García Aldrete (Psocodea: Psocomorpha: Ptiloneuridae) - Cutrim, Marcelo; Da Silva Neto, Alberto Moreira; Aldrete, Alfonso N. García; Rafael, José Albertino (Zootaxa, 2021)
A new species of Loneura named as Loneura willineri n. sp. is described from Bolivia, and and variation in the venation of the fore and hindwings discussed. Both sexes of Loneura meridionalis García Aldrete are described, inclulding variation in the fore and hindwing venation, and this species is withdrawn from synonymy with Loneura boliviana, a species now considered a nomen dubium.